Investigasi Pengaruh Lingkungan Kerja pada Produktivitas Kerja Karyawan - Luluh Abdilah Kurniawan (Asosiasi Ahli Administrasi Indonesia, 2020)
This investigation is to prove the effectiveness of the working environment for the employees. The object of this research is the employees of a trading company. The total population is the same as the total sample. This research uses a descriptive method with multiple regression analysis. The result of the study shows that a safe, comfortable, and neatly organized working environment affect the employees’ work productivity. Air circulation, air temperature, workspace, room layout are the dimensions that greatly affect the employees’ work productivity.